Quantification of the European industrial heat demand by branch and temperature level. (19th October 2015) - Naegler, Tobias; Simon, Sonja; Klein, Martin; Gils, Hans Christian
Summary: We present the first comprehensive estimate of the final energy demand for heat in all EU28 member states for the reference year 2012, differentiated by temperature levels, comparing two different approaches. Two different calculation approaches based on different data sets yielded estimates of the total final energy demand for heat in the EU28 of 8150 PJ and 8518 PJ in 2012, respectively. Approach 1 distinguishes between three different process heat (PH) temperature levels and results in final energy demand for heat <100°C: 2077 PJ, 100–400°C: 2214 PJ and >400°C: 3859 PJ. The second approach distinguishes between low temperature space heat and hot water (<100°C: 1161 PJ) and four different PH temperature levels with a resulting energy demand of <100°C: 1027 PJ, 100–500°C: 1785 PJ, 500–1000°C: 1679 PJ and >1000°C: 2865 PJ. The high share of high‐temperature heat illustrates the limits to the potential decarbonisation of industrial thermal processes with renewable energy sources such as (non‐concentrating) solar thermal, geothermal or environmental heat. Therefore specific information on required temperature levels is of the essence. This, in turn, points out the relevance of renewable electricity and synthetic fuels based on renewable power for a significant reduction of CO2 emissions from the industry sector in Europe. Considering current data quality, it is recommended to develop a consistent, comprehensive methodology to significantly improve the data basis on industrial heat demand. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We estimate the final energy demand for heat in the EU28 member states in 2012, differentiated by temperature levels with two different calculation approaches based on different data sets The second approach distinguishes between low temperature space heat and hot water (< 100°C: 1, 161 PJ) and four different process heat temperature levels with a resulting final energy demand of 1, 027 PJ (< 100°C), 1, 785 PJ (100–500°C), 1, 679 PJ (500–1000°C) and 2, 865 PJ (> 1000°C), respectively.